Comparison of the international Burn Injury Database nurse dependency tool with the Safer Nursing Care Tool: Observational study. (November 2021) - Leaver, Jane; Cook, Robert; Dunn, Ken; Dee, Philip; Ejtehadi, Hora Davari
Abstract: Background: Safe and effective nurse staffing is widely recognised as an important issue to ensure quality patient care and reduce mortality. There are many nurse dependency tools described in the literature but no gold standard tool that can be used in all specialities. In burn care there are even fewer burn specific tools and none reported for use in the UK to date. The international Burn Injury Database contains routinely collected information about burn injuries, including nurse dependency data which so far has not been reported in the literature. Objective: This study aimed to confirm whether the international Burn Injury Database nurse dependency tool can be used to measure nurse dependency in burn services. Methods: Over a two week period, nurses in three burn services scored the nurse dependency of their burn injured patients daily using the international Burn Injury Database Nurse Dependency Tool and the Safer Nursing Care Tool. Additionally all the participating nurses were asked to score three fictional case studies using the same two tools to assess inter-rater reliability. Results: There was a statistically significant positive correlation between the international Burn Injury Database Nurse Dependency Tool and the Safer Nursing Care Tool scores (ρ = 0.87, 95% CI = 0.82–0.90). The case study scores showed a similar correlation pattern as the daily comparison recordings. The inter-rater reliability between the participants was comparable for both the international Burn Injury Database Nurse Dependency Tool (α =0.74, CI = 0.71–0.77) and the Safer Nursing Care Tool (α =0.79, CI = 0.76–0.81). Psychological support variable had the weakest correlation with the nurse dependency tools and the lowest agreement between nurses. Conclusion: This is the first report in the literature of the international Burn Injury Database Nurse Dependency Tool, the results of which suggest that it does measure aspects of nurse dependency and thus could be a valuable tool in the battle to ensure safe staffing. The good inter-rater reliability between the nurses, regardless of the nurse dependency tool used, should give confidence to nurses and managers using the dependency data to influence staffing.